Emergency and elective caesarean sections: comparison of maternal and fetal outcomes in a suburban tertiary care hospital in Puducherry - Diana, Valsa; Tipandjan, Arun (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of the current study was to compare the maternal and fetal outcomes of emergency and elective caesarean deliveries. Methods: A prospective case comparative study was conducted at the Government Maternity Hospital, Department of Obstetrics and Gynaecology, Puducherry, from August 2005 to July 2006. Results: A total of 301 caesarean deliveries occurred during the study period. The percentages of the primi-gravida as well as the nulli-parous women were significantly higher among emergency caesarean section than that in elective caesarean section (χ2=12.52, P<0.0001). The percentages of previous caesarean sections was significantly higher among those who had elective caesarean than those had emergency caesarean section in the present delivery (χ2=14.73, P=0.0001). Among emergency caesarean section 25.8% had abdominal distension, whereas it was present only in 8.7% of the elective cases. Of the 16 new born with postnatal complications in the emergency group, 14 died, one had convulsion and the remaining one was a stillbirth. In the elective group there were 4 deaths. Conclusions: It was inferred that both elective and emergency caesarean imposes certain complications to the mother and the fetes. However, maternal and fetal complications were felt very high in emergency caesarean than elective. Proper planning can help obstetric practitioners to avoid complications.